THE EFFECT OF JOB PROMOTIONS AND POSITION MUTATIONS ON JOB SATISFACTION OF EMPLOYEES OF THE DIRECTORATE GENERAL OF TAXES WITH WORK-LIFE BALANCE AS AN INTERVENING VARIABLE: Case Study on the Regional Office of DGT D.I. Yogyakarta - Saputri, Raden Roro Brian Geta Hari; Priyastiwi, Priyastiwi; Tjahjono, Achmad (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2024)
This study aims to analyze the influence of position promotions and position mutations on job satisfaction of employees of the DGT Regional Office of the Special Region of Yogyakarta. In addition, this study also analyzes the indirect influence of job promotions and job mutations on job satisfaction through work-life balance as an intervening variable. The method used is a descriptive quantitative approach with the Structural Equation Model (SEM) analysis technique. Data was collected through a questionnaire and analyzed using Smart PLS 3.2.9 software. The population of this study is all employees of the DGT Regional Office of the Special Region of Yogyakarta, with a sample of 67 employees who occupy the positions of Objection Reviewer and implementer, selected using the purposive sampling method. The results of the study show that position promotion has a positive effect on employee job satisfaction. On the other hand, position mutation has a significant negative effect on job satisfaction. Work-life balance has a positive and significant effect on job satisfaction and mediates the influence of job promotion on job satisfaction significantly. However, work-life balance does not mediate the influence of position mutations on job satisfaction.